Sustainable Machining Using Eco-Friendly Cutting Fluids: A Review - Pankaj Kumar; Amit Kumar Jain; Prem Kumar Chaurasiya; Damodar Tiwari; Anitha Gopalan; Joshuva Arockia Dhanraj; Jenoris Muthiya Solomon; Aravinth Sivakumar; Karthikeyan Velmurugan; Johannex Fefeh Rushman (Advances in Materials Science and Engineering)
The base fluids of eco-friendly cutting fluids should contain some vegetable oil. Due to their eco-friendly, thermal, and tribological qualities, these types of machining fluids are becoming increasingly popular among researchers throughout the world. The authors summarized published research studies on the use of eco-friendly machining fluids (including nanofluids) in various metal removal processes such as turning, milling, grinding, and drilling in this review paper. The impact of several biodegradable oil-based machining fluids on performance metrics such as surface irregularity, machining force, tool wear, power demand, and temperature-induced during the machining process is also explored in this paper. According to the previous and current literature, using an eco-friendly nano machining fluid results in better surface features, less cutting tool wear, lower cutting force, less power required, and lower machining zone temperature during the machining operation due to superior cooling and lubrication properties.